Study of the Coherence Functions of Light in a Jaynes-Cummings non-linear System - Ruiz-Rocha, Yurimar; Gonzaléz, Julio; Villamil, Pablo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In this work, a two-level quantum dot inside of a cavity with a non-linear Kerr-type medium and a single mode of the electromagnetic field quantized was considered. The master equation was constructed taking into account dissipative processes, with the non-linear Kerr term, and it was numerically solved for the stationary state, taking into account the temperature. On the basis of these results, observable aspects of the state of the light were calculated, such as the average number of photons and the spectrum of photoluminescence, and the quantum-classical characteristics of the state of the light were determined by means of the calculation of the coherence functions of the second-order photons.